A novel and environmental friendly synthetic route for hydroxypyrrolidines using zeolites. (15th January 2019) - Fan, A.; Chuah, G.K.; Jaenicke, Stephan
Abstract: A critical step in the synthesis of the hydroxypyrrolidines, 1, 4-dideoxy-1, 4-imino-l -lyxitol and 1, 4-dideoxy-1, 4-imino-d -lyxitol, from the correspondingd -sugars is the synthesis of O -methyl 2, 3- O -isopropylidenepentofuranoses. Instead of applying homogeneous catalysis process with conventional inorganic acid catalysts like HCl and HClO4, it was found that heterogeneous catalysis using zeolites could be used for the one-pot synthesis of O -methyl 2, 3- O -isopropylidenepentofuranoses directly fromd -sugars, MeOH and acetone at mild condition. The best catalyst was H-beta zeolite containing a Si/Al molar ratio of 150, where a yield of >83% was obtained. The overall yields of the five-step procedure to 1, 4-dideoxy-1, 4-imino-l -lyxitol and 1, 4-dideoxy-1, 4-imino-d -lyxitol were 57% and 50%, respectively. This synthetic procedure has several advantages such as competitive overall yield, reduced number of steps, and mild reaction conditions. Furthermore, the zeolite catalyst can be easily recovered from the reaction mixture and reused with no loss of activity. Graphical abstract: Highlights: In this work, we invented a novel and environmental friendly synthetic route for hydroxylpyrrolidines using zeolites and some Highlights as below: 1. Instead of conventional homogeneous inorganic acid catalysts like HCl and HClO4, we applied a solid acid catalyst, zeolites for the one-pot synthesis of O -methyl 2, 3- O -isopropylidenepentofuranoses directly fromd -sugars, MeOH and acetone at mild condition. 2. Instead of using NaBH3 CN for the reduction of the intermediate imine to amine with the formation of toxic HCN, we also invented the reduction reaction by using in-situ molecular H2 generated from NH3 solution and Zn dust. 3. The overall yields of the five-step synthetic route to 1, 4-dideoxy-1, 4-imino-l -lyxitol and 1, 4-dideoxy-1, 4-imino-d -lyxitol were very competitive 57% and 50%, respectively. 4. The overall synthetic protocol has several advantages such as competitive overall yield, reduced number of steps, and mild reaction conditions. Furthermore, the zeolite catalyst can be easily recovered from the reaction mixture and reused with no loss of activity.